ANALISIS KEBUTUHAN GURU DAN SISWA TENTANG PENGGUNAAN BUKU POP UP PADA MATA PELAJARAN IPAS BAGI KELAS V DI SEKOLAH DASAR - Najwa Haya Karin; Uswatun Hasanah; Petrus Paulus Mbette Suhendro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the needs for using pop-up book media in the IPAS (Ilmu Pengetahuan Alam dan Sosial) subject for fifth-grade students at SDN 01 Pinang Ranti Pagi. The background of this research is the low learning outcomes of students, particularly in understanding abstract concepts in the IPAS subject, which is due to the limited use of interactive and engaging learning media. The learning process is still dominated by the use of textbooks, PowerPoint, and YouTube, which do not accommodate the visual and kinesthetic learning styles typical of elementary school students. This descriptive qualitative research involved 32 students and class teachers through interviews and questionnaires to explore their experiences and needs related to learning media. The results indicate that students require concrete, attractive, and interactive media that can increase learning motivation and make abstract materials easier to understand. The study proposes the development of a pop-up book integrated with barcodes linked to audio explanations to enhance student engagement and comprehension. This research contributes to the development of contextual and student-centered learning media in elementary education, especially in IPAS subjects, and addresses a research gap by deeply exploring students’ and teachers’ perspectives on the use of innovative instructional tools.